De novo variant of TRRAP in a patient with very early onset psychosis in the context of non-verbal learning disability and obsessive-compulsive disorder: a case report - Mavros, Chrystal F. (BMC Med Genet, 2018)
BACKGROUND: TRRAP encodes a multidomain protein kinase that works as a genetic cofactor to influence DNA methylation patterns, DNA damage repair, and chromatin remodeling. TRRAP protein is vital to early neural developmental processes, and variants in this gene have been associated with schizophrenia and childhood disintegrative disorder. CASE PRESENTATION: Here, we report on a patient with a de novo nonsynonymous TRRAP single-nucleotide variant (EST00000355540.3:c.5957G > A, p.Arg1986Gln) and early onset major depression accompanied by a psychotic episode (before age 10) that occurred in the context of longer standing nonverbal learning disability and a past history of obsessions and compulsions. CONCLUSIONS: The de novo variant and presentation of very early onset psychosis indicate a rare Mendelian disorder inheritance model. The genotype and behavioral abnormalities of this patient are reviewed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12881-018-0711-9) contains supplementary material, which is available to authorized users.